Hospital management of hyperglycemia in the context of COVID-19: evidence-based clinical considerations - Mendes, Thiago Bosco [UNESP] (2022)
The COVID-19 pandemic led to an unprecedented crisis, and early on, it has been shown that diabetes is an important risk factor for complications and mortality in infected patients, as demonstrated by several studies. Moreover, hyperglycemia, regardless of whether patients have diabetes, is associated with poorer outcomes, which suggests that adequate monitoring and treatment of elevated glycemia in the hospital setting can improve patient outcomes. In patients with COVID-19, glycemic control may be impaired as a consequence of the infection itself (aggravating pre-existing diabetes and potentially precipitating new-onset diabetes), inflammation, or corticosteroid use—a well-established therapy to reduce COVID-19 complications, especially in the intensive care unit. This article reviews the link between diabetes and hyperglycemia, and COVID-19, with a brief review of potential mechanisms, along with emerging evidence on the effect of glycemic control on COVID-19 outcomes, especially in hospital settings.